L'innovation musicale dans la poésie de Ali bin Abdul Rahman Bin Abielbichre Sicilien - Lire dans les Mouwashahat du Maroc suscité - - Bouzidi, Salim (Milev Journal of Research and Studies, 2017)
The present research deals with the musical innovation within the poetry of Ali bin Abdul Rahman bin Abi El Bisher El Sikilli. The latter stood as one of the pioneer Maghriban poets who wrote terza rima in a way that allows generating more than one metre by relying on approximate metrics of the light metre, the sand metre and the root meter in both its complete and partial picture. This represents a Maghriban attempt to renew the religious terza rima which appeared in the Arab Maghreb, and was known as the country metrics.